Biodegradation potential of Gordonia spp. on polypropylene and polystyrene: enhanced degradation through pretreatment - Yan Zhu; Hongzhe Wang; Hongzhe Wang; Jing Bai; Yanjie Qi; Dongfei Han (Frontiers in Microbiology, 2025)
IntroductionAs extensively utilized synthetic polymers, polypropylene (PP) and polystyrene (PS) have raised significant environmental concerns due to their persistent accumulation in ecosystems.MethodsTo enhance biodegradation efficiency, we implemented a dual pretreatment approach combining thermal activation and fenton’s reagent oxidation prior to microbial treatment. Through a systematic 50-day incubation experiment with single-strain cultures of five Gordonia strains (Gordonia polyisoprenivorans B251, Gordonia polyisoprenivorans B253, Gordonia hydrophobica 4.134, Gordonia humi 4.135, and Gordonia sihwensis LQ21), we quantitatively evaluated the degradation performance using four complementary analytical methods: mass loss quantification, attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), and scanning electron microscopy (SEM) and surface water contact angle.ResultsNotably, Gordonia polyisoprenivorans B253 demonstrated remarkable degradation capabilities, as evidenced by: (1) characteristic chemical modifications including hydroxyl group formation (3,280 cm−1), carbon-carbon double bond generation (1,640 cm−1), and ether group appearance (1,100 cm−1) in ATR-FTIR spectra; (2) pronounced surface erosion patterns observed via SEM; and (3) significant mass reduction (1.927% ± 0.038% of PS) compared to controls. Comparative analysis revealed that combined thermal-fenton pretreatment enhanced biodegradation efficiency about by 1.3-fold compared to untreated samples, suggesting synergistic effects between physicochemical pretreatment and biological degradation. Genomic characterization of B253 identified putative catabolic enzymes, including alkane hydroxylases, cytochrome P450 systems, alcohol-dehydrogenase, styrene monooxygenase and epoxide hydrolase potentially responsible for polymer breakdown.DiscussionThis work advances plastic biodegradation by identifying novel PP/PS-degrading Gordonia species, establishing an effective pretreatment protocol, and providing genomic insights into biodegradation pathways. These findings contribute to developing sustainable solutions for managing persistent plastic waste. These products or metabolites from the degradation of PP and PS plastics can be further extracted and processed into new plastic raw materials or other valuable products, facilitating the recycling of plastic resources. This approach not only decreases reliance on fossil resources, but also mitigates energy consumption and carbon emissions during of plastics production. Thus, it promotes the development of green and sustainable plastics industry and contributes to the establishment of a circular economy. Furthermore, we believe there is also great potential for addressing plastic pollution through various integrated treatment methods.